Feeding the World in 2050. Issue 11 (29th October 2014) - Bohn, Martin
Abstract : This month, ASA, CSSA, and SSSA have teamed up with the American Society of Agricultural and Biological Engineers (ASABE) to produce a joint issue under the theme "Feeding the World in 2050." More than 20 articles were written on various topics addressing the challenges we face in feeding the world, a handful of which appear in this issue of CSA News magazine (for the full presentation, please see ASABE's Resource magazine here: www.asabe.org/publications/resource‐magazine.aspx ). In addition to the joint articles, we also are including a profile this issue of the 2014 World Food Prize winner, Sanjaya Rajaram, a Fellow of ASA and CSSA.